Identifikasi Sebaran Kadar Ni Menggunakan Metode Hand Auger Desa Molino, Kabupaten Morowali Utara, Sulawesi Tengah - Moh Al-Fayedh; Muh Kasim; Ronal Hutagalung; Alifia Widya Warapsari Badaru (Universitas Negeri Gorontalo, 2025)
One of the regions in Indonesia with potential laterite nickel deposits is North Morowali, where the MTosu Formation, composed of Cretaceous-aged ultramafic rocks, is found. This study aims to identify the distribution of laterite and nickel content using data from Hand Auger analysis. The methods used include field observations, Hand Auger sampling, and geochemical analysis through X-Ray Fluorescence (XRF). The research area features two main geomorphological units: structural steep hills and structural gentle hills. Its stratigraphy consists of lherzolite and serpentinite units. The dominant geological structure trends northeast-southwest, following a linear pattern. Laterite distribution in the area is controlled by topography. Nickel content is categorized into three zones: high, medium, and low. XRF analysis of Hand Auger samples indicates that high nickel concentrations are located in the southwest and extend northeast across the study area.